Preparation method of hot-pressed carbon quantum dot / Nafion composite proton exchange membrane
Carbon quantum dots were prepared by hydrothermal synthesis and hot-pressed composite with Nafion membrane, which solved the problems of high cost of Nafion membrane and strong dependence on water, and achieved a high-performance and low-cost proton exchange membrane.
Patent Information
- Application Number
- CN202411707845.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
The existing Nafion proton exchange membrane is costly and highly dependent on water, resulting in a sharp attenuation of performance in low humidity environments.
Carbon quantum dots were prepared by hydrothermal synthesis method, and the carbon quantum dots were compounded with the Nafion membrane by hot pressing to form a new hot pressed carbon quantum dot/Nafion composite proton exchange membrane.
It reduces the cost of the proton exchange membrane, improves the stability and mechanical properties of the membrane, and enhances the proton conductivity, making it suitable for applications in low humidity environments.
Smart Images

Figure BDA0005154939570000081 
Figure BDA0005154939570000082 
Figure HDA0005154939640000011
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a novel hot-pressed carbon quantum dot / Nafion composite proton exchange membrane, belonging to the field of fuel cell proton exchange membranes. Background Art
[0002] With the development of mankind, the large-scale use of fossil energy has caused today's serious global environmental crisis. Today, when we advocate harmonious coexistence between man and nature and sustainable development models, more and more new clean energy sources are attracting people's attention, especially hydrogen energy. Fuel cells, as a device that can convert hydrogen energy into electrical energy, have become an important technical path. Fuel cells have received widespread attention from academia and industry due to their many advantages. The development and utilization of new energy is an important means to effectively solve problems such as energy shortages and environmental pollution. Fuel cells, as a green and environmentally friendly energy conversion device, play an important role in the development and utilization of new energy.
[0003] As one of the core components of proton exchange membrane fuel cells (PEMFC), the performance of proton exchange membrane (PEM) directly affects whether the proton exchange membrane fuel cell can have excellent power output and service life. For example, the Nafion membrane, which is the most widely used commercial membrane, has an excessive reliance on water molecules for proton conductivity, which leads to a rapid attenuation of its conductivity in anhydrous environments and low humidity conditions.
[0004] At present, Nafion proton exchange membrane still has the following shortcomings. First, the cost of Nafion membrane is relatively high in practical applications. Second, it is highly dependent on water. In a low-humidity environment, the performance decays sharply. In this regard, my current treatment method is to add inorganic fillers to improve the hydrophilic water-locking ability of the membrane under low-humidity operation. Therefore, the waterless environment and low-humidity application of Nafion membrane in fuel cell equipment have been studied. In order to solve the application of Nafion membrane in waterless and low-humidity conditions, we believe that carbon quantum dots are one of the most effective modified materials, which have good hydrophilic properties and easy functional modification. Carbon quantum dots are also easy to prepare and cheap. Therefore, it is urgent to develop a membrane material with low price, simple preparation process and good comprehensive performance. Summary of the invention
[0005] The present invention aims at the defects of the current proton exchange membrane, such as high cost, poor performance under low humidity conditions and pollution to the environment, and provides a novel hot-pressed carbon quantum dot / Nafion proton exchange membrane material preparation method, and adopts a hydrothermal synthesis method to prepare fluorescent carbon quantum dots to improve the performance of the Nafion composite membrane; the method first adds urea granules and malonic acid powder into deionized water to fully dissolve them, puts them into a high-pressure reactor, and then sets the oven temperature, hydrothermally reacts to synthesize carbon quantum dots, and then pre-treats the Nafion membrane into a methanol aqueous solution to fully swell it, put it on a pressing plate, set the hot press parameters, drip carbon quantum dots, make it uniformly flat on the membrane, and then hot press for 1-2 minutes, change the hot press times, and obtain carbon quantum dots / Nafion composite membranes with different contents added. The preparation process of the present invention is simple, the reaction conditions are mild, and the prepared proton exchange membrane has high stability, mechanical properties and high proton conductivity at the same time under the condition of reduced cost.
[0006] The technical solution of the present invention is as follows:
[0007] (1) Preparation of carbon quantum dots
[0008] Adding urea granules and malonic acid powder into deionized water to fully dissolve and stir to obtain a mixed aqueous solution; placing the obtained mixed aqueous solution into a hydrothermal synthesis reactor, and then into a blast drying oven, and performing a hydrothermal reaction at 150-400° C. for 2-6 hours to obtain a carbon quantum dot solution; taking out the reactor and allowing it to cool naturally to room temperature, and then placing it into a high-speed centrifuge for centrifugation at 8000-10000 r / min to obtain a carbon quantum dot solution;
[0009] It is further preferred that the mass ratio of urea to malonic acid is 1.5-2:3-3.5; it is further preferred that every 1.5-2 g of urea corresponds to 30 ml of deionized water.
[0010] (2) Preparation of carbon quantum dots / Nafion composite proton exchange membrane
[0011] First, cut the Nafion membrane, such as the commercial DuPont Nafion212 membrane, for pretreatment. The treatment process is as follows: a. Cut the Nafion membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in a 3%-5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in a 0.3-0.6mol / L, preferably 0.5mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use. The pretreated membrane is then placed in a methanol aqueous solution and swelled for at least 0.5 hours to enlarge its pores, and then placed on a hot press. The hot press is set to a temperature of 60-80°C, preferably 70°C, and a pressure of 6-9MPa, preferably 8MPa. The carbon quantum solution is dripped onto the swollen Nafion membrane to make it uniform and flat, and hot pressing is maintained for 1-2 minutes. Then, the carbon quantum dot solution and hot pressing are repeated. The operation is repeated for a total of 15-45 times, for example, 15 times, 30 times, and 45 times respectively, and then dried at 80°C for 24 hours to obtain a new hot-pressed carbon quantum dot / Nafion composite proton exchange membrane.
[0012] In the above-mentioned novel method for preparing a hot-pressed carbon quantum dot / Nafion composite proton exchange membrane, the amount of carbon quantum dot solution added each time is: 0.5-1 ml of carbon quantum dot solution is added per square centimeter of Nafion membrane, and the concentration of the carbon quantum dot solution is 0.05-0.1 g / ml; according to the number of repeated additions of the carbon quantum dot solution and hot pressing, the final mass content of the carbon quantum dots infiltrated into the membrane is 0.05%-1.5%.
[0013] In the above-mentioned novel method for preparing hot-pressed carbon quantum dots / Nafion composite proton exchange membrane, the method described is a hot pressing method.
[0014] The particle size distribution of the prepared carbon quantum dots is in the range of 1.5-3.0 nm, and the average particle size is 2.5 nm.
[0015] In the above-mentioned novel method for preparing hot-pressed carbon quantum dots / Nafion composite proton exchange membrane, after being treated with methanol solution, the Nafion membrane swells and becomes larger from the original pore size of 1-5 nm, allowing the carbon dots to enter better.
[0016] The essential features of the present invention are:
[0017] Urea contains nitrogen, and malonic acid is rich in carbon and carboxyl groups. The raw materials are cheap and readily available, so the one-step hydrothermal carbonization of urea and malonic acid to prepare carbon dots is simple, low-cost, and has the potential to achieve large-scale mass production. Carbon quantum dots tend to be highly compatible with Nafion membranes, and the abundant hydrophilic functional groups in carbon quantum dots, such as hydroxyl (-OH) and carboxyl (-COOH) groups, can serve as proton hopping sites, thereby enhancing the ionic conductivity of Nafion. Moreover, the added carbon quantum dot filler mainly promotes proton conductivity and mechanical properties by forming hydrogen bonds between the large number of hydrophilic groups in the carbon quantum dots and the sulfonic acid groups in the Nafion matrix.
[0018] The beneficial effects of the present invention are:
[0019] 1. The carbon quantum dot proton exchange membrane described in the present invention has low cost, simple modification process, and does not involve complicated chemical experiments, laying a solid foundation for large-scale preparation of composite membranes.
[0020] 2. Methanol is a volatile organic solvent with the characteristics of low price and volatility. Methanol aqueous solution can increase the surface area of the membrane, resulting in larger pore size, so that the carbon quantum dots can be better attached to the membrane.
[0021] 3. The prepared CQDs are hydrophilic inorganic materials with good stability and low price. In addition, the hydroxyl groups of CQDs can form a hydrogen bond network with the sulfonic acid groups in the Nafion matrix, significantly improving the mechanical properties of the proton exchange membrane and enhancing the durability of the proton exchange membrane.
[0022] 4. The proton exchange membrane prepared by the present invention has good thermal stability; the TG analyzer shows that the membrane remains stable at 300°C, so the operating temperature range is at least above 100°C or even up to 300°C; the infrared spectrum shows that the introduction of carbon quantum dots will not affect the structure of Nafion, and the proton exchange membrane has high conductivity and excellent mechanical properties.
[0023] 5. The composite proton exchange membrane prepared by the present invention is obtained by hot pressing technology, and the cross section of the membrane is observed by SEM scanning electron microscope. The cross section of the prepared proton exchange membrane is dense and stable, which can meet the application in fuel cells and is suitable for commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Comparison of carbon quantum dots prepared from malonic acid and urea under sunlight and ultraviolet light
[0025] Figure 2 TEM transmission electron microscopy image of carbon quantum dots prepared from malonic acid and urea
[0026] Figure 3Comparison of SEM scanning cross-section electron microscopy of carbon quantum dot composite film and control group film
[0027] Figure 4 Thermogravimetric analysis (TG) characterization diagram of carbon quantum dot composite film and control group film
[0028] Figure 5 Infrared analysis (FI-TR) characterization diagram of carbon quantum dot composite film and control group film
[0029] Figure 6 The graph shows the mechanical properties of the carbon quantum dot composite film and the control group film. DETAILED DESCRIPTION
[0030] The examples given below are intended to exemplify the present invention but do not limit the present invention, the scope of which is defined by the claims.
[0031] Embodiment 1:
[0032] (1) At room temperature, 1.5 g of urea granules and 3 g of malonic acid powder were added to 30 ml of deionized water to fully dissolve and stirred to obtain a mixed aqueous solution;
[0033] (2) placing the mixed aqueous solution described in step (1) into a 50 ml polytetrafluoroethylene (PTFE) liner, placing it into a hydrothermal synthesis reactor, and then placing it into a blast drying oven, and performing a hydrothermal reaction at 200° C. for 4 h to obtain a carbon quantum dot solution;
[0034] (3) taking out the reactor and letting it cool naturally to room temperature, then putting it into a high-speed centrifuge, setting it to 10,000 r / min, and centrifuging it for about 20 minutes to obtain a carbon quantum dot solution;
[0035] (4) Cut the commercial DuPont Nafion212 membrane and perform pretreatment. The treatment process is as follows: a. Cut the Nafion212 membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in 300 ml of 5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in 300 ml of 0.5 mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in 300 ml of deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use.
[0036] (5) Prepare a pretreated membrane, place it in a methanol-water solution for 0.5 h to swell it and enlarge its pores, then place it on a hot press. Set the temperature of the hot press to 70°C and about 8 MPa. Add carbon quantum solution on the swollen Nafion membrane to make it uniform and flat. The carbon quantum dot solution bulges about 2 mm. Keep hot pressing for 1-2 minutes, do 15 times, and then dry it at 80°C for 24 h to obtain a composite proton exchange membrane doped with 0.5 wt% carbon quantum dots.
[0037] Embodiment 2:
[0038] (1) At room temperature, 1.75 g of urea granules and 3.25 g of malonic acid powder were added to 30 ml of deionized water to fully dissolve and stirred to obtain a mixed aqueous solution;
[0039] (2) placing the mixed aqueous solution described in step (1) into a 50 ml polytetrafluoroethylene (PTFE) liner, placing it into a hydrothermal synthesis reactor, and then placing it into a blast drying oven, and performing a hydrothermal reaction at 200° C. for 4 h to obtain a carbon quantum dot solution;
[0040] (3) taking out the reactor and letting it cool naturally to room temperature, then putting it into a high-speed centrifuge, setting it to 10,000 r / min, and centrifuging it for about 20 minutes to obtain a carbon quantum dot solution;
[0041] (4) Cut the commercial DuPont Nafion212 membrane and perform pretreatment. The treatment process is as follows: a. Cut the Nafion212 membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in 300 ml of 5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in 300 ml of 0.5 mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in 300 ml of deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use.
[0042] (5) Prepare a pretreated membrane, place it in a methanol-water solution for 0.5 h to swell it and enlarge its pores, then place it on a hot press. Set the temperature of the hot press to 70°C and about 8 MPa. Add carbon quantum solution on the swollen Nafion membrane to make it uniform and flat. The carbon quantum dot solution bulges about 2 mm. Keep hot pressing for 1-2 minutes, do hot pressing 30 times, and then dry it at 80°C for 24 h to obtain a composite proton exchange membrane doped with carbon quantum dots at 1 wt%.
[0043] Embodiment 3:
[0044] (1) At room temperature, 2 g of urea granules and 3.5 g of malonic acid powder were added to 30 ml of deionized water to fully dissolve and stirred to obtain a mixed aqueous solution;
[0045] (2) placing the mixed aqueous solution described in step (1) into a 50 ml polytetrafluoroethylene (PTFE) liner, placing it into a hydrothermal synthesis reactor, and then placing it into a blast drying oven, and performing a hydrothermal reaction at 200° C. for 4 h to obtain a carbon quantum dot solution;
[0046] (3) taking out the reactor and letting it cool naturally to room temperature, then putting it into a high-speed centrifuge, setting it to 10,000 r / min, and centrifuging it for about 20 minutes to obtain a carbon quantum dot solution;
[0047] (4) Cut the commercial DuPont Nafion212 membrane and perform pretreatment. The treatment process is as follows: a. Cut the Nafion212 membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in 300 ml of 5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in 300 ml of 0.5 mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in 300 ml of deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use.
[0048] (5) Prepare a pretreated membrane, place it in a methanol-water solution for 0.5 h to swell it and enlarge its pores, then place it on a hot press, set the temperature of the hot press to 70°, about 8 MPa, add carbon quantum solution on the swollen Nafion membrane to make it uniform and flat, and the carbon quantum dot solution bulges about 2 mm, and hot press for 1-2 minutes, hot press 45 times, and then dry it at 80°C for 24 h to obtain a composite proton exchange membrane doped with carbon quantum dots at 1.5 wt%.
[0049] Embodiment 4:
[0050] (1) At room temperature, 1.75 g of urea granules and 3.25 g of malonic acid powder were added to 30 ml of deionized water to fully dissolve and stirred to obtain a mixed aqueous solution;
[0051] (2) placing the mixed aqueous solution described in step (1) into a 50 ml polytetrafluoroethylene (PTFE) liner, placing it into a hydrothermal synthesis reactor, and then placing it into a blast drying oven, and performing a hydrothermal reaction at 150° C. for 6 h to obtain a carbon quantum dot solution;
[0052] (3) taking out the reactor and letting it cool naturally to room temperature, then putting it into a high-speed centrifuge, setting it to 10,000 r / min, and centrifuging it for about 20 minutes to obtain a carbon quantum dot solution;
[0053] (4) Cut the commercial DuPont Nafion212 membrane and perform pretreatment. The treatment process is as follows: a. Cut the Nafion212 membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in 300 ml of 5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in 300 ml of 0.5 mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in 300 ml of deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use.
[0054] (5) Prepare a pretreated membrane, place it in a methanol-water solution for 0.5 h to swell it and enlarge its pores, then place it on a hot press. Set the temperature of the hot press to 70°C and about 8 MPa. Add carbon quantum solution on the swollen Nafion membrane to make it uniform and flat. The carbon quantum dot solution bulges about 2 mm. Keep hot pressing for 1-2 minutes, do hot pressing 30 times, and then dry it at 80°C for 24 h to obtain a composite proton exchange membrane doped with carbon quantum dots at 0.05 wt%.
[0055] Embodiment 5:
[0056] (1) At room temperature, 1.75 g of urea granules and 3.25 g of malonic acid powder were added to 30 ml of deionized water to fully dissolve and stirred to obtain a mixed aqueous solution;
[0057] (2) placing the mixed aqueous solution described in step (1) into a 50 ml polytetrafluoroethylene (PTFE) liner, placing it into a hydrothermal synthesis reactor, and then placing it into a blast drying oven, and performing a hydrothermal reaction at 300° C. for 3 h to obtain a carbon quantum dot solution;
[0058] (3) taking out the reactor and letting it cool naturally to room temperature, then putting it into a high-speed centrifuge, setting it to 10,000 r / min, and centrifuging it for about 20 minutes to obtain a carbon quantum dot solution;
[0059] (4) Cut the commercial DuPont Nafion212 membrane and perform pretreatment. The treatment process is as follows: a. Cut the Nafion212 membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in 300 ml of 5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in 300 ml of 0.5 mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in 300 ml of deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use.
[0060] (5) Prepare a pretreated membrane, place it in a methanol-water solution for 0.5 h to swell it and enlarge its pores, then place it on a hot press. Set the temperature of the hot press to 70°C and about 8 MPa. Add carbon quantum solution on the swollen Nafion membrane to make it uniform and flat. The carbon quantum dot solution bulges about 2 mm. Keep hot pressing for 1-2 minutes, do hot pressing 30 times, and then dry it at 80°C for 24 h to obtain a composite proton exchange membrane doped with carbon quantum dots at 0.1 wt%.
[0061] Embodiment 6:
[0062] (1) At room temperature, 1.75 g of urea granules and 3.25 g of malonic acid powder were added to 30 ml of deionized water to fully dissolve and stirred to obtain a mixed aqueous solution;
[0063] (2) placing the mixed aqueous solution described in step (1) into a 50 ml polytetrafluoroethylene (PTFE) liner, placing it into a hydrothermal synthesis reactor, and then placing it into a blast drying oven, and performing a hydrothermal reaction at 400° C. for 2 h to obtain a carbon quantum dot solution;
[0064] (3) taking out the reactor and letting it cool naturally to room temperature, then putting it into a high-speed centrifuge, setting it to 10,000 r / min, and centrifuging it for about 20 minutes to obtain a carbon quantum dot solution;
[0065] (4) Cut the commercial DuPont Nafion212 membrane and perform pretreatment. The treatment process is as follows: a. Cut the Nafion212 membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in 300 ml of 5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then soak the Nafion membrane in 300 ml of 0.5 mol / L sulfuric acid solution and boil it for 1 hour; d. Finally, soak the Nafion membrane in 300 ml of deionized water and boil it for 1 hour, and then soak the membrane material in deionized water for later use.
[0066] (5) Prepare a pretreated membrane, place it in a methanol-water solution for 0.5 h to swell it and enlarge its pores, then place it on a hot press. Set the temperature of the hot press to 70°C and about 8 MPa. Add carbon quantum solution on the swollen Nafion membrane to make it uniform and flat. The carbon quantum dot solution bulges about 2 mm. Keep hot pressing for 1-2 minutes, do hot pressing 30 times, and then dry it at 80°C for 24 h to obtain a composite proton exchange membrane doped with carbon quantum dots at 0.2 wt%.
[0067] The following table summarizes the preparation parameters in the embodiments of the present invention.
[0068]
[0069] The following table is a performance comparison between the composite membrane of the present invention and the commercial Nafion212 proton exchange membrane
[0070]
[0071] The proton conductivity was tested using a CHI electrochemical workstation under the conditions of a four-electrode AC impedance method, a test frequency of 0.1 Hz-1 MHz, a test range of 30-80° C., and 100% RH.
[0072] The mechanical properties of the membrane material can be measured by the stress-strain curve. The stress-strain curve test is as follows: first, cut the membrane into strips of 0.5 cm × 4 cm, clamp the strips tightly on the universal tensile tester fixture, select the stress-strain test module, room temperature, stretching rate 5 mm / min, and draw the graph after calculation and processing based on the obtained data points.
[0073] By comparing under the same test conditions, we can see that when the number of hot pressing of modified carbon quantum dots in Example 2 is 30 times and the doping carbon quantum dots is 1wt%, the proton conductivity of the composite membrane tested at 30°C is 109mS / cm and the maximum tensile stress is 22.2MPa. It can be seen that compared with commercial Nafion212, the introduction of carbon quantum dots can enhance the proton conductivity and mechanical properties of the membrane; at the same time, Figure 4 It can be seen from the thermogravimetric analysis diagram that the membrane remains stable at 300°C, and the proton exchange membrane of this invention can be used at a temperature of at least 100°C; and because the carbon quantum dots added in the present invention have hydrophilic groups such as COOH / OH, in summary, the membrane of the present invention has good performance, a simple preparation method, a high proton conductivity, better durability, and a lower application cost than commercial Nafion membranes.
Claims
1. A method for preparing a hot-pressed carbon quantum dot / Nafion composite proton exchange membrane, characterized in that: The following steps are involved: (1) Preparation of carbon quantum dots Adding urea granules and malonic acid powder into deionized water to fully dissolve and stir to obtain a mixed aqueous solution; placing the obtained mixed aqueous solution into a hydrothermal synthesis reactor, and then into a blast drying oven, and performing a hydrothermal reaction at 150-400° C. for 2-6 hours to obtain a carbon quantum dot solution; taking out the reactor and allowing it to cool naturally to room temperature, and then placing it into a high-speed centrifuge for centrifugation at 8000-10000 r / min to obtain a carbon quantum dot solution; (2) Preparation of carbon quantum dots / Nafion composite proton exchange membrane First, cut the Nafion membrane, such as the commercial DuPont Nafion212 membrane, and perform pretreatment. The treatment process is as follows: a. Cut the Nafion membrane into the required size and peel off the sealing protective films on both sides; b. Soak the Nafion membrane in a 3%-5% hydrogen peroxide solution and boil it for 1 hour, and rinse it with deionized water; c. Then, the Nafion membrane is immersed in a 0.3-0.6mol / L, preferably 0.5mol / L sulfuric acid solution and boiled for 1 hour; d. Finally, the Nafion membrane is immersed in deionized water and boiled for 1 hour, and then the membrane material is immersed in deionized water for standby use; the pretreated membrane is then placed in a methanol aqueous solution to swell for at least 0.5 hours to enlarge its pores, and then placed on a hot press, the hot press is set to a temperature of 60-80°C, preferably 70°C, and a pressure of 6-9MPa, preferably 8MPa, and a carbon quantum solution is dripped on the swollen Nafion membrane to make it uniform and flat, and hot pressing is maintained for 1-2 minutes, and then the carbon quantum dot solution and hot pressing are repeated, and the operation is repeated a total of 15-45 times, for example, 15 times, 30 times, and 45 times, respectively, and then dried at 80°C for 24 hours to obtain a new hot-pressed carbon quantum dot / Nafion composite proton exchange membrane.
2. The method according to claim 1, characterized in that In step (1), the mass ratio of urea to malonic acid is 1.5-2:3-3.
5.
3. The method according to claim 1, characterized in that Step (1) Every 1.5-2 g of urea corresponds to 30 ml of deionized water.
4. The method according to claim 1, characterized in that The particle size distribution of carbon quantum dots is in the range of 1.5-3.0 nm, and the average particle size is 2.5 nm.
5. The method according to claim 1, characterized in that In step (2), the amount of the carbon quantum dot solution added each time is as follows: 0.5-1 ml of the carbon quantum dot solution is added per square centimeter of the Nafion membrane, and the concentration of the carbon quantum dot solution is 0.05-0.1 g / ml.
6. The method according to claim 1, characterized in that In step (2), the carbon quantum dots solution is repeatedly added dropwise and hot pressed for a number of times, so that the final mass content of the carbon quantum dots infiltrated into the membrane is 0.05%-1.5%.
7. The method according to claim 1, characterized in that After being treated with methanol solution, the Nafion membrane swells from its original pore size of 1-5nm to allow the carbon dots to enter better.
8. A hot pressed carbon quantum dot / Nafion composite proton exchange membrane prepared according to the method of any one of claims 1 to 7.
9. Application of the hot-pressed carbon quantum dots / Nafion composite proton exchange membrane prepared by the method according to any one of claims 1 to 7, with an operating temperature of 100°C-300°C.
Citation Information
Patent Citations
Fuel battery proton exchange film with anti-penetration layer and its making method
CN101237056A
Bacterial cellulose-Nafion sandwich proton exchange membrane and preparation and application thereof
CN102694139A
Nitrogen doped carbon quantum dot as well as preparation method and application thereof
CN103756675A
Sulfonated polyimide-Nafion composite membrane and preparation method thereof
CN108428917A
Application of ionic liquid in preparation of nitrogen-doped carbon quantum dots, and preparation method and application of nitrogen-doped carbon quantum dots
CN109796006A